1) =0,4х-1+6х+3,6=6,4х+2,6, если х = 0,4, то 6,4*0,4+2,6=5,16
2) =1,5х-1+2,8-4,2х=1,8-2,7х, при х= -0,2 1,8-2,7*(-0,2)= 1,8+0,54=2,34
3)=1,2х-1,8+3,6х-5,4=4,8х-7,2, при х=-0,1 4,8*(-0,1)-7,2=-0,48-7,2=-7,68
4)5-2(3х-4)=4х-3 5)3-4(2х-5)=2-6х 6)6-3 (2х-5)=2х-7
5-6х+8=4х-3 3-8х+20=2-6х 6-6х+15=2х-7
16=10х 21=2х 28=8х
х=1,6 х=10,5 х=3,5
7)9-2(3х-4)=3х+8 8)11+4 (х-3)=9х- 15
9-6х+8=3х+8 11+4х-12= 9х-15
9=9х 14=5х
х=1 х=2,8
2t^2+t-1=0
t1=(-1-3)/4=-1
t2=(-1+3)/4=1/2
Вернёмся к замене
sinx=-1
x=-Π/2+2Πn, n€Z
sinx=1/2
x1=Π/6+2Πm, m€Z
x2=5Π/6+2Πm, m€Z
ответ: -Π/2+2Πn, n€Z; Π/6+2Πm, 5Π/6+2Πm, m€Z
2) 6cos^2x+cosx-1=0
Пусть t=cosx, где t€[-1;1], тогда
6t^2+t-1=0
t1=(-1-5)/12=-1/2
t2=(-1+5)/12=1/3
Вернёмся к замене:
cosx=-1/2
x=+-arccos(-1/2)+2Πn, n€Z
cosx=1/3
x=+-arccos(1/3)+2Πm, m€Z
ответ: +-arccos(-1/2)+2Πn, n€Z; +-arccos(1/3)+2Πm, m€Z
3) 2cos^2x+sinx+1=0
2(1-sin^2x)+sinx+1=0
-2sin^2x+sinx+3=0
Пусть t=sinx, где t€[-1;1], тогда
-2t^2+t+3=0
t1=(-1-5)/-4=-1,5 посторонний, т.к. t€[-1;1]
t2=(-1+5)/-4=-1
Вернёмся к замене
sinx=-1
x=Π/2+2Πn, n€Z
ответ: Π/2+2Πn, n€Z